A Pedagogical Model of Strategic Management. Part 1: Presentation of the Model (GESTIÓN Y TENDENCIAS, 2024)
Faced with the growing challenges companies encounter for their development and sustainability, it becomes necessary to manage them from a strategic perspective, focusing their efforts on understanding their environment in order to achieve a better competitive position based on their resources and capabilities. Within this framework, the article proposes a model to facilitate the teaching and understanding of the key concepts, stages, and components of strategic business management. This pedagogical model holds that strategic management is carried out in two stages with their respective components: strategy formulation, and strategic implementation and control. The purpose of this article is to present the pedagogical model, which will be complemented by further related articles.
Keywords: pedagogical model; sustainability; strategic management